Predictors of Seeking Care for Influenza-Like Illness in a Novel Digital Study. (22nd December 2022) - Chawla, Devika; Benitez, Alejandra; Xu, Hao; Whitehill, Victoria; Tadesse-Bell, Sara; Shapiro, Allison; Ramirez, Ernesto; Scherer, Kelly; Foschini, Luca; Drawnel, Faye; Clinch, Barry; Prunotto, Marco; et al.
Abstract: Background: Previous research has estimated that >50% of individuals experiencing influenza-like illness (ILI) do not seek health care. Understanding factors influencing care-seeking behavior for viral respiratory infections may help inform policies to improve access to care and protect public health. We used person-generated health data (PGHD) to identify factors associated with seeking care for ILI. Methods: Two observational studies (FluStudy2020, ISP) were conducted during the United States 2019–2020 influenza season. Participants self-reported ILI symptoms using the online Evidation platform. A log-binomial regression model was used to identify factors associated with seeking care. Results: Of 1667 participants in FluStudy2020 and 47 480 participants in ISP eligible for analysis, 518 (31.1%) and 11 426 (24.1%), respectively, sought health care. Participants were mostly female (92.2% FluStudy2020, 80.6% ISP) and aged 18–49 years (89.6% FluStudy2020, 89.8% ISP). In FluStudy2020, factors associated with seeking care included having health insurance (risk ratio [RR], 2.14; 95% CI, 1.30–3.54), more severe respiratory symptoms (RR, 1.53; 95% CI, 1.37–1.71), and comorbidities (RR, 1.37; 95% CI, 1.20–1.58). In ISP, the strongest predictor of seeking care was high symptom number (RR for 6/7 symptoms, 2.14; 95% CI, 1.93–2.38). Conclusions: Using PGHD, we confirmed low rates of health care–seeking behavior for ILI and show that having health insurance, comorbidities, and a high symptom burden were associated with seeking health care. Reducing barriers in access to care for viral respiratory infections may lead to better disease management and contribute to protecting public health.